Melcior Febrer, poeta i dramaturg del Baix Maestrat de la primera meitat del segle XVII. - QUEROL COLL, ENRIC (Scripta, 2018)
This paper incorporates a new name to the list of Valencian Baroque poets: Melcior Febrer: (Vinaròs, 1578 -- Traiguera, ? 1648). The main part of the corpus of his works, unattended by the critics, is preserved in the manuscript 3895 (Biblioteca Nacional de España). This volume contains his own compositions, mainly written in Spanish, as well as others of his favourite poets, thus creating a highly representative collection of the poetical taste of the time. Besides this group of referential pan-Hispanic writers, the volume also contains a series of works generated in the Valencian area due to Febrer and some of his literary friends and acquaintances, such as Marc Antoni Ortí, Vicent Esquerdo or Francesc Cros. Due to its metaliterary interest, an edition of the poem Resposta mia a una carta en valencià escrita per el señor y amich March Antoni Ortí is provided in appendix.